Longitudinal antibody and T cell responses in Ebola virus disease survivors and contacts: an observational cohort study. Issue 4 (April 2021) - Thom, Ruth; Tipton, Thomas; Strecker, Thomas; Hall, Yper; Akoi Bore, Joseph; Maes, Piet; Raymond Koundouno, Fara; Fehling, Sarah Katharina; Krähling, Verena; Steeds, Kimberley; Varghese, Anitha; Bailey, Graham; et al.
Summary: Background: The 2013–16 Ebola virus disease epidemic in west Africa caused international alarm due to its rapid and extensive spread resulting in a significant death toll and social unrest within the affected region. The large number of cases provided an opportunity to study the long-term kinetics of Zaire ebolavirus-specific immune response of survivors in addition to known contacts of those infected with the virus. Methods: In this observational cohort study, we worked with leaders of Ebola virus disease survivor associations in two regions of Guinea, Guéckédou and Coyah, to recruit survivors of Ebola virus disease, contacts from households of individuals known to have had Ebola virus disease, and individuals who were not knowingly associated with infected individuals or had not had Ebola virus disease symptoms to serve as negative controls. We did Zaire ebolavirus glycoprotein-specific T cell analysis on peripheral blood mononuclear cells (PBMCs) on location in Guinea and transported plasma and PBMCs back to Europe for antibody quantification by ELISA, functional neutralising antibody analysis using live Zaire ebolavirus, and T cell phenotype studies. We report on the longitudinal cellular and humoral response among Ebola virus disease survivors and highlight potentially paucisymptomatic infection. Findings: We recruited 117 survivors of Ebola virus disease, 66 contacts, and 23 negative controls. The mean neutralising antibody titre among the Ebola virus disease survivors 3–14 months after infection was 1/174 (95% CI 1/136—1/223). Individual results varied greatly from 1/10 to more than 1/1000 but were on average ten times greater than that induced after 1 month by single dose Ebola virus vaccines. Following reactivation with glycoprotein peptide, the mean T cell responses among 116 Ebola virus disease survivors as measured by ELISpot was 305 spot-forming units (95% CI 257–353). The dominant CD8+ polyfunctional T cell phenotype, as measured among 53 Ebola virus disease survivors, was interferon γ+, tumour necrosis factor+, interleukin-2–, and the mean response was 0·046% of total CD8+ T cells (95% CI 0·021–0·071). Additionally, both neutralising antibody and T cell responses were detected in six (9%) of 66 Ebola virus disease contacts. We also noted that four (3%) of 117 individuals with Ebola virus disease infections did not have circulating Ebola virus-specific antibodies 3 months after infection. Interpretation: The continuous high titre of neutralising antibodies and increased T cell response might support the concept of long-term protective immunity in survivors. The existence of antibody and T cell responses in contacts of individuals with Ebola virus disease adds further evidence to the existence of sub-clinical Ebola virus infection. Funding: US Food & Drug Administration, Horizon 2020 EU EVIDENT, Wellcome, UK Department for International Development. Translation: For the French translation of the abstract see Supplementary Materials section.